ISSUES OF IMPROVING THE TAX STRATEGY IN UZBEKISTAN BASED ON THE EXPERIENCE OF FOREIGN COUNTRIES (American Journal of Business Management, Economics and Banking, 2025)
The development and implementation of a new tax strategy in Uzbekistan is of fundamental importance for ensuring the country's sustainable economic development, improving the business environment, simplifying tax administration, and strengthening social justice. This process will ensure that the tax system responds to modern challenges and will serve to increase the country's economic potential in the coming years.